Skaning laserowy jako technologia wielu zastosowań - pomiary geodezyjne na potrzeby architektów = Laser scanning as multi-use technology - geodetic measurements for the architecture purposes - Błaszczak-Bąk, Wioleta; Sobieraj-Żłobińska, Anna; Szulwic, Jakub; Minkowska, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Laser scanning makes it possible to acquire a point cloud, which can be developed and used in various stages of investment, e.g: by performing simple measurements on point cloud or on the model created on the basis of this point cloud, the development of digital models of scanned objects, their visualizations and interior design.
Keywords: skaning laserowy; chmura punktów; wymiarowanie; wizualizacja; laser scanning; point cloud; dimensioning; visualization